Dip TIPS as a facile and versatile method for fabrication of polymer foams with controlled shape, size and pore architecture for bioengineering applications - Kasoju, Naresh; Kubies, Dana; Kumorek, Marta M; Kříž, Jan; Fábryová, Eva; Machová, Lud'ka; Kovářová, Jana; Rypáček, František (PloS one, 2014)
The porous polymer foams act as a template for neotissuegenesis in tissue engineering, and, as a reservoir for cell transplants such as pancreatic islets while simultaneously providing a functional interface with the host body. The fabrication of foams with the controlled shape, size and pore structure is of prime importance in various bioengineering applications. To this end, here we demonstrate a thermally induced phase separation (TIPS) based facile process for the fabrication of polymer foams with a controlled architecture. The setup comprises of a metallic template bar (T), a metallic conducting block (C) and a non-metallic reservoir tube (R), connected in sequence T-C-R. The process hereinafter termed as Dip TIPS, involves the dipping of the T-bar into a polymer solution, followed by filling of the R-tube with a freezing mixture to induce the phase separation of a polymer solution in the immediate vicinity of T-bar; Subsequent free-drying or freeze-extraction steps produced the polymer foams. An easy exchange of the T-bar of a spherical or rectangular shape allowed the fabrication of tubular, open- capsular and flat-sheet shaped foams. A mere change in the quenching time produced the foams with a thickness ranging from hundreds of microns to several millimeters. And, the pore size was conveniently controlled by varying either the polymer concentration or the quenching temperature. Subsequent in vivo studies in brown Norway rats for 4-weeks demonstrated the guided cell infiltration and homogenous cell distribution through the polymer matrix, without any fibrous capsule and necrotic core. In conclusion, the results show the "Dip TIPS" as a facile and adaptable process for the fabrication of anisotropic channeled porous polymer foams of various shapes and sizes for potential applications in tissue engineering, cell transplantation and other related fields.
Keywords: Mercury; Calorimetry, Differential Scanning; povrchové vlastnosti; Temperature; potkani inbrední BN; molekulová hmotnost; poréznost; teplota; Tissue Scaffolds; Microscopy, Electron, Scanning; zvířata; diferenciální skenovací kalorimetrie; časové faktory; polymery; Rats, Inbred BN; Polymers; bioinženýrství; tkáňové podpůrné struktury; Male; mikroskopie elektronová rastrovací; Phase Transition; změna skupenství; Bioengineering; Porosity; Animals; mužské pohlaví; Time Factors; rtuť; Surface Properties; Molecular Weight